Английские заимствования во французском языке (на материале женских журналов) - Кобринец, О.С. (Культура народов Причерноморья, 2013)
Статья посвящена анализу английских заимствований во французском языке. В ней
рассматриваются основные причины проникновения англицизмов, сферы наибольшего их употребления
и степень частоты использования в современном французском языке. Сравниваются данные из словарей
по количеству английских заимствований с XVIII века и до сих пор. Выделены и охарактеризованы
основные типы англицизмов, а также проанализированы основные репрезентативные особенности
английских заимствований на материале модных женских журналов.
Ключевые слова: французский язык, заимствования, виды англицизмов, англицизмы в женских
журналах. Статтю присвячено аналізу англійських запозичень у французькій мові. У ній розглядаються
основні причини проникнення англіцизмів, сфери найбільшого їх вживання і ступінь частоти
використання у сучасній французькій мові. Порівнюються дані зі словників за кількістю англійських
запозичень з XVIII століття і до сьогодні. Виокремлені й охарактеризовані основні типи англіцизмів, а
також проаналізовані основні репрезентативні особливості англійських запозичень на матеріалі
модних жіночих журналів.
Ключові слова: французька мова, запозичення, види англіцизмів, англіцизми у жіночих журналах. This article is aimed at the English borrowings in the French language on the material of women's
magazines. In this research the main causes of penetration of anglicisms, the scope of most of their usage and
the frequency of their using in modern French are analyzed. The information from the dictionaries of the English
borrowings from the XVIII century up to now is compared. Our analysis shows that the stream of English
borrowings has been increased considerably at the beginning of the XXI century according to the process of
globalization, the development of new technologies, the Internet. First of all, this phenomenon is revealed in the
areas of business, science, the media, particularly in women's magazines.
Our research allowed to divide the аnglicisms of the French language into 3 large groups: almost inevitable
(naming the new realities and objects); borrowings represented by French synonym (French lexical doublets)
and borrowings as a fashion sign.
From a linguistic point of view, borrowings are divided into 6 categories: semantic, lexical, syntactic,
morphological, phonetic and graphic.
Among the semantic groups "Fashion and Shopping", "Style", "Colors", "Clothing and Footwear", "Beauty
Industry", "Music", "Movie, Show Business", "Art", "Food and Cuisine" "News and Society," "Professions",
"Communication" the largest number of borrowings have been identified in the spheres "Fashion and
Shopping", "Style", "News and Society". This fact is explained by the type of women’s magazines by focusing on
a particular audience.
The main features of anglicisms in women's magazines are their abundance in the headlines of articles, titles
and subheadings; the conjugation of the English verbs according to French pattern of the first group or its usage
without any modification; the usage of verbs and nouns as adjectives; the usage of the English nouns without
any changes but with the addition of the article.
Keywords: the French language, borrowings, the types of anglicisms, English borrowings in French women's
magazines.